Altered glucose metabolism in default mode network and prefrontal circuit in patients with Kallmann syndrome - Chunqing Zhou; Xueying Wang; Meichao Men; Xiaoping Yi; Ke Cao; Weidan Pu; Marcus Hacker; Xiang Li; Min Zhao (EJNMMI Research)
Abstract Background This study delineates brain metabolic signatures underlying neuroendocrine-psychosocial interactions in Kallmann syndrome (KS), a rare genetic disorder characterized by congenital hypogonadism and anosmia. In this prospective case-control study, 30 KS patients and 30 matched healthy controls (HCs) underwent brain [18F]FDG PET scans, sex hormone assays, and standardized neuropsychological assessments. A voxel-wise group comparison analysis was conducted to identify clusters of brain metabolic patterns between KS patients and HCs. Subsequently, correlation and mediation analyses were performed to investigate the interrelationships and mediating effect among brain metabolic patterns, sex hormone levels, and psychosocial factors. Results We identified six hypermetabolic clusters in KS patients, predominantly located in the fronto-limbic system and the default mode network (DMN) in KS patients. These clusters of hypermetabolism were significantly associated fertility anxiety scale (FAS), health information avoidance scale (HIAS) and health information overload scale (HIOS). In addition, mediation analysis indicated that bilateral basal ganglia hypermetabolism acted as a significant mediator between HIAS and FAS (β = 0.274, P = 0.031). Conclusion Patients with KS exhibited a distinct hypermetabolism pattern in the DMN-prefrontal circuit, which functionally bridges neuroendocrine dysfunction and reproductive health anxiety.